Corruption in Nigeria:/ the way out - Ilorah, Peter (Abuja, Nigeria: Praise Peter Communications, 2009)
The book discusses corruption in Nigeria with particular reference to the views expressed by anit-crusaders; the role of anti-corruption stakeholders and finally recommendations on how to end corruption in Nigeria.
lje 5/9/13
Loans
Keywords: Nigeria-Corrupt Practices